Analisis Pembiayaan Bermasalah Bank Wakaf Mikro Pada Pelaku Usaha Mikro Kecil (UMK) di BWM Pondok Pesantren As’ad Seberang Kota Jambi - Diah Fardila; Rafiqi .; Ary Dean Amri (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This research aims to find out the causes of problematic financing at Micro Waqf Banks, to find out the impact of problematic financing at Micro Waqf Banks and to understand the handling of BWM settlements for problematic financing at As'ad Islamic Boarding School Micro Waqf Banks. The research method used is qualitative. The data sources used in this research are primary and secondary. The data collection techniques used in this research are observation and interviews. The results of this research show that (1) The causes of Problematic Financing in Micro Waqf Banks are intentional elements such as the poor character of customers who deliberately do not want to pay installments and unintentional elements such as a decline in economic conditions and disasters occurring. (2) The impact of problematic financing on Micro Waqf Banks, namely decreasing BWM income, the impact of a bad image not only impacting the intra-institution but later external parties will also have a negative view of the Institution. employee time and energy spent going directly to the customer's location. (3) Handling the BWM Settlement for Problematic Financing of the As'ad Islamic Boarding School Micro Waqf Bank, namely by having a jointly responsible group, visiting the customer's residence (silaturrahmi) and providing an extension of time to the customer.